2021
DOI: 10.1186/s12944-021-01527-4
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acids and triglyceride change in the gallbladder bile of gallstone patients with pancreaticobiliary reflux

Abstract: Background Pancreaticobiliary reflux (PBR) causes chronic inflammation of the gallbladder mucosa and changes in the bile components, which are known to promote gallstone formation. This study aimed to investigate the bile biochemistry changes in gallstone patients with PBR and provide new clues for research on the involvement of PBR in gallstone formation. Methods Patients undergoing surgery for gallstones between December 2020 and May 2021 were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…All these factors play a positive role in gallstone formation [ 38 ]. Previous study showed that the total FFA content in the bile of patients with PBR was significantly higher than that in the control group [ 39 ]. Interestingly, here we found that palmitic acid increased significantly in patients with PBR, which might play an active role in gallstone formation.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors play a positive role in gallstone formation [ 38 ]. Previous study showed that the total FFA content in the bile of patients with PBR was significantly higher than that in the control group [ 39 ]. Interestingly, here we found that palmitic acid increased significantly in patients with PBR, which might play an active role in gallstone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In bile, the presence of FFA has been demonstrated [ 33 , 34 ]. The elevated levels of bile FFAs were found to be an important and main risk factor for gallbladder wall thickening process [ 35 ]. FFAs are well-known risk factors of cardiovascular diseases (CVDs) [ 36 ] and have closely relationship with the events of metabolic syndromes (MetS), such as obesity and type 2 diabetes mellitus (T2DM).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the bile of controls, the bile from patients with gallstones had higher total free fatty acid content, more palmitic acid, more stearic acid, more linoleic acid and arachidonic acid [41]. Xiang et al [42] suggest that pancreaticobiliary reflux induced an increase in FFAs and triglycerides in the gallbladder bile is a cause of gallstone formation.…”
Section: Fatty Acidsmentioning
confidence: 99%